A temperature‐mediated two‐step saccharification process enhances maltose yield from high‐concentration maltodextrin solutions. (22nd December 2020) - Li, Caiming; Kong, Haocun; Yang, Qianwen; Gu, Zhengbiao; Ban, Xiaofeng; Cheng, Li; Hong, Yan; Li, Zhaofeng
Abstract: BACKGROUND: Designing a high‐concentration (50%, w/w) maltodextrin saccharification process is a green method to increase the productivity of maltose syrup. RESULTS: In this study, a temperature‐mediated two‐step process using β ‐amylase and pullulanase was investigated as a strategy to improve the efficiency of saccharification. During the saccharification process, both pullulanase addition time and temperature adjustment greatly impacted the final maltose yield. These results indicated that an appropriate β ‐amylolysis in the first stage (the first 8 h) was required to facilitate saccharification process, with the maltose yield of 8.46% greater than that of the single step saccharification. Molecular structure analysis further demonstrated that a relatively low temperature (50 °C), as compared with a normal temperature (60 °C), in the first stage resulted in a greater number of chains polymerized by at least seven glucose units and a less heterogeneity system within the residual substrate. The molecular structure of the residual substrate might be beneficial for the subsequent cooperation between β ‐amylase and pullulanase in the following 40 h (second stage). CONCLUSION: Over a 48 h saccharification, the temperature‐mediated two‐step process dramatically increased the conversion rate of maltodextrin and yielded significantly more maltose and less byproduct, as compared with a constant‐temperature process. The two‐step saccharification process therefore offered an efficient and green strategy for maltose syrup production in industry. © 2020 Society of Chemical Industry